2019
DOI: 10.1152/jn.00636.2018
|View full text |Cite
|
Sign up to set email alerts
|

Theta-gamma cascades and running speed

Abstract: Oscillations in the hippocampal local field potential at theta and gamma frequencies are prominent during awake behavior and have demonstrated several behavioral correlates. Both oscillations have been observed to increase in amplitude and frequency as a function of running speed. Previous investigations, however, have examined the relationship between speed and each of these oscillation bands separately. Based on energy cascade models where “…perturbations of slow frequencies cause a cascade of energy dissipa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(84 citation statements)
references
References 128 publications
7
76
1
Order By: Relevance
“…Recent investigations of hippocampal LFP in rats show a strong relation between energy input into the hippocampus (as inferred based on rat speed) and the nonlinear character of neural activity [Sheremet et al, 2016b,a, 2019b,a]. Both spectra and bispectra are well ordered with input power, as parameterized by rat speed.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent investigations of hippocampal LFP in rats show a strong relation between energy input into the hippocampus (as inferred based on rat speed) and the nonlinear character of neural activity [Sheremet et al, 2016b,a, 2019b,a]. Both spectra and bispectra are well ordered with input power, as parameterized by rat speed.…”
Section: Motivationmentioning
confidence: 99%
“…If the latter were true, then collective activity would be indeed at most of a secondary concern. However, as observations and hypotheses accumulate that contradict the “multiplexing” model, such as the degeneracy and role of turbulence and self-organized criticality in collective neural activity (e.g., Edelman, 1987, Edelman and Gally, 2001, Beggs and Plenz, 2003, Shew et al, 2011, Beggs and Timma, 2012, Sheremet et al, 2018a, 2019b and others), or perhaps simply due to the growing interest in mesoscale processes, the capabilities of the Wilson and Cowan [1972a, 1973] model are bound to undergo further scrutiny.…”
Section: Short Review Of Neural Population Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hippocampal CA1 gamma power and frequency also increase as a function of running speed [42][43][44] . Accordingly, the stratum lacunosum-moleculare of the CA1 region has been shown to exhibit a strong positive correlation between theta-gamma coupling and running speed 45 , suggesting that the speed signal of theta-modulated gamma inputs are conveyed from the entorhinal cortex to the hippocampus 46,47 . Consistent with this notion, the majority of speed cells in the MEC are suggested to encode speed prospectively, whereas those in the hippocampus are suggested to encode speed retrospectively 10 .…”
mentioning
confidence: 99%
“…Bicoherence is an advanced signal processing technique capable of tracking the neuronal non-linearity and non-Gaussian signals underlying brain functions (Bullock et al, 1997;Darvas et al, 2009;Li et al, 2009Li et al, , 2013. Many studies has shown that this technique can quantify the strength of non-linear phase-phase CFC [i.e., quadratic phase coupling (QPC)] between frequency components of the LFP signal (von Stein et al, 2000;Wang et al, 2007;Darvas et al, 2009;Sheremet et al, 2019). The neural generators of QPC have been reported for object coding in single neuron, in which different features of an object (e.g., size and angular speed) are encoded by a multiplicative process (Gabbiani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%